Holistyczne kompetencje zawodowe studentów pielęgniarskich studiów magisterskich = The holistic nursing professional competence of students graduate - Brodowicz-Król, Magdalena; Zarzycka, Danuta; Stadnicka, Sabina; Bartoń, Elżbieta (Journal of Education, Health and Sport, 2016)
Brodowicz-Król Magdalena, Zarzycka Danuta, Stadnicka Sabina, Bartoń Elżbieta. Holistyczne kompetencje zawodowe studentów pielęgniarskich studiów magisterskich = The holistic nursing professional competence of students graduate. Journal of Education, Health and Sport. 2016;6(8):113-127. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59880 http://ojs.ukw.edu.pl/index.php/johs/article/view/3736 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Holistyczne kompetencje zawodowe studentów pielęgniarskich studiów magisterskich The holistic nursing professional competence of students graduate 1 Magdalena Brodowicz-Król, 1 Danuta Zarzycka, 1 Sabina Stadnicka, 2 Elżbieta Bartoń 1 Katedra i Zakład Pielęgniarstwa Pediatrycznego Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie ul. Prof. A. Gębali 6, 20-093 Lublin 2 Katedra i Klinika Neurochirurgii Samodzielny Publiczny Szpital Kliniczny nr 4 w Lublinie Ul. Jaczewskiego 8 20-954 Lublin Autor do korespondencji: Magdalena Brodowicz-Król Katedra i Zakład Pielęgniarstwa Pediatrycznego Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie ul. Prof. A. Gębali 6, 20-093 Lublin e-mail: brmagdalena@gmail.com Tel. 662 980 412 Streszczenie Wprowadzenie: We współczesnym pielęgniarstwie umiejętność sprawowania profesjonalnej opieki nad pacjentem przez studentów szczególnie studiów magisterskich jest istotą procesu kształcenia. Natomiast postrzeganie pacjenta w systemie opieki w sposób holistyczny, a zatem jako indywidualnego podmiotu funkcjonującego co najmniej w wymiarze biologicznym, społecznym, psychicznym, duchowym i kulturowym, zgodnie z zasadami etyki jest jednym z wymiarów profesjonalizmu. W akademickim kształceniu pielęgniarek duże znaczenie przywiązuje się do kształtowania umiejętności pielęgniarskich tworzących możliwość holistycznego traktowania osoby pacjenta. Cel pracy: Określenie kompetencji zawodowych holistycznego postrzegania pacjenta przez studentów I roku studiów magisterskich kierunku pielęgniarstwo. Materiał i metoda: Badania przeprowadzono wśród studentów kierunku pielęgniarstwo Uniwersytetu Medycznego w Lublinie. Wiek ankietowanych mieścił się w przedziałach 21-22 (32,6%) i23-38 (67,4%) lat. Kobiety stanowiły większość badanych (97,1%) zdecydowanie mniejszą grupę stanowili mężczyźni (2,9%). Metodą badawczą, którą zastosowano w badaniu, był sondaż diagnostyczny. Wykorzystanym narzędziem badawczym była Skala Holistycznych Kompetencji Pielęgniarskich (The Holistic Nursing Competence Scale –HNCS). Skala ta ocenia kompetencje pielęgniarskie, składa się z dwóch podskal i zawiera łącznie 36 twierdzeń. Podskala HNCS A zawiera 7 pozycji, ocenia postępowanie pielęgniarskie w życiu codziennym oraz podskala HNCS B zawiera 29 pozycji, ocenia holistyczne kompetencje pielęgniarskie. Drugim narzędziem była Skala Rozwoju Kompetencji Pielęgniarskich (Ascent to Nursing Competence Scale- ACS). Skala jest zbudowana z pytań zamkniętych, uporządkowanych w trzech podskalach. Pierwsza podskala bada współpracę w relacji student - opiekun/nauczyciel (W1-W6) składa się z 6 pozycji, druga ocenia potrzebę przynależności studenta do grupy (B1-B17) składa się z 17 pozycji, trzecia, trzecia pozwala na ocenę wiedzy i umiejętności zawodowych studenta pielęgniarstwa (L1-L13) zawiera 13 pozycji [23]. Bazę danych utworzono i analizy statystyczne przeprowadzono w oparciu o oprogramowanie komputerowe Statistica 9.1. (StatSoft, Polska). Zgromadzone informacje analizowano w oparciu o następujące testy: U Manna-Whitneya (Z), został zastosowany by zbadać różnice pomiędzy dwiema grupami. Do sprawdzenia zależności pomiędzy zmiennymi wykorzystano korelację rang Spermana (R). W analizie przyjęto poziom istotności p<0,05 wskazujący na istnienie istotnych statystycznie różnic lub zależności. Wyniki: Kompetencje holistyczne badanych studentów osiągnęły wysokie wartości. Najwyższe wartości dotyczyły „Wskazanie na uchybienia pozostałych pracowników służby zdrowia w celu zapewniania bezpiecznej opieki nad pacjentem” (HNCS B9.-5,6), „Zapewnienie opieki pielęgniarskiej przy jednoczesnym zachowaniu zgodności z obowiązującymi przepisami” (HNCS B16.-5,6), „Dołożenie wszelkich starań, aby zdobyć i przyswoić aktualną wiedzę i umiejętności niezbędne w praktyce pielęgniarskiej” (HNCS B26.-5,6). W badaniach stwierdzono istotne statystycznie różnice między oceną pielęgniarskich kompetencji holistycznych (HNCS) a rozwojem kompetencji zawodowych (ACS) oraz pomiędzy podskalą ACS W (potrzeba przynależności studenta- pielęgniarki do grupy) a podskalą HNCS B (holistyczne kompetencje pielęgniarskie p= 0,04. Wnioski: Wyniki badań pozwalają na sformułowanie wniosku, że studenci kierunku pielęgniarstwo, posiadają wyższy poziom holistycznych kompetencji nabytych w trakcie kształcenia praktycznego na studiach zawodowych niż kompetencji osobistych, które student sam nabywa w wyniku osobistego rozwoju. W analizie wykazano związek na poziomie istotnym statystycznie pomiędzy pielęgniarskimi kompetencjami holistycznymi a kompetencjami zawodowymi. Zmienne społeczno-demograficzne (wiek, praca, nauka) nie korelują z pielęgniarskimi kompetencjami holistycznymi ani z rozwojem kompetencji zawodowych. Słowa kluczowe: student, pielęgniarstwo, kompetencje zawodowe, holistyczne kompetencje zawodowe. The holistic competences of the graduate students, faculty of nursing Abstract Background: In modern nursing ability to exercise professional patient care by students in particular Master is the essence of the educational process. In contrast, the perception of the patient care system in a holistic way and, therefore, as an individual entity functioning at least in the dimension of biological, social, mental, spiritual and cultural, in accordance with the principles of ethics is one of the dimensions of professionalism. The academic education of nurses attaches great importance to the development of nursing skills creating the possibility of a holistic treatment of a human patient. Aim: Determine the professional competence of a holistic perception of the patient through the first year students of the nursing graduate. Material and Methods: The study was conducted among students of nursing at the Medical University of Lublin. Age of respondents was in the intervals 21-22 (32.6%) i23-38 (67.4%) years. Women accounted for the majority of respondents (97.1%), a much smaller group were men (2.9%). Research method, which was used in the study was a diagnostic survey. Deployed as a research tool was a holistic scale of Competence Nursing (The Holistic Nursing Competence Scale -HNCS). This scale assesses the competence of nursing consists of two subscales and contains a total of 36 claims. HNCS A subscale includes 7 items, evaluates nursing treatment in everyday life and subscale HNCS B contains 29 items, assesses the competence of holistic nursing. The second instrument was the scale of Competence Development of Nursing (Ascent to Nursing Competence Scale-ACS). The scale is composed of closed questions, arranged in three subscales. The first subscale explores cooperation relationship student - tutor / teacher (W1-W6) consists of 6 positions, the second assesses the need to belong student group (B1-B17) consists of 17 items, the third, the third allows for the assessment of knowledge and skills nursing student (L1-L13) contains 13 items [23]. The database was created and statistical analyzes were performed based on the software Statistica 9.1. (StatSoft, Poland). The information collected was analyzed using the following tests: Mann-Whitney U (Z), it was used to test for differences between the two groups. To check the relationship between variables used Spearman rank correlation (R). In the analysis, the significance level of p <0.05 indicating the existence of statistically significant differences or relationships. Results: Competence holistic surveyed students reached high values. The highest values related to "provide nursing care centered on the patient with respect for their dignity and rights" (HNCS B 10), "treat each patient individually, while respecting its cultural background and values while maintaining the lack of any prejudice" (HNCS B 17) and "communication with patients according to their age, origin and cultural value system" (HNCS B 27). The study found statistically significant differences between the assessment of holistic nursing competence (HNCS) and the development of professional competence (ACS) and between subscale ACS (need to belong student - nurses group) and subscale HNCS B (holistic nursing competencies p = 0.04. Conclusions: The test results allow us to conclude that students of nursing, have a higher level of holistic skills acquired during practical training at university professional than personal competencies that a student he acquires as a result of personal development. The analysis demonstrated the relationship of statistically significant between holistic nursing competencies and professional competence. Socio-demographic variables (age, work, education) do not correlate with holistic nursing competencies or the development of professional competence. Keywords: student, nursing, competence, holistic competence.